2002
DOI: 10.1093/jnen/61.12.1085
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathological Changes in a Mouse Model of Progressive Myoclonus Epilepsy: Cystatin B Deficiency and Unverricht-Lundborg Disease

Abstract: Progressive myoclonus epilepsy of the Unverricht-Lundborg type (EPM1) is a recessively inherited neurodegenerative disease caused by loss-of-function mutations in the gene encoding cystatin B, a cysteine protease inhibitor. Mice with disruptions in this gene display myoclonic seizures, progressive ataxia, and cerebellar pathology closely paralleling EPMI in humans. To provide further insight into our understanding of EPM1, we report pathological findings in brains from cystatin B-deficient mice. In addition to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
70
0
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 27 publications
8
70
0
2
Order By: Relevance
“…16 The mice also show loss of cerebellar granule cells due to apoptotic cell death, 16 neuronal atrophy and apoptosis outside the cerebellum and gliosis. 17 In mice double-deficient for CSTB and cathepsin B, the amount of cerebellar apoptosis is significantly decreased, suggesting that cathepsin B contributes to the apoptotic phenotype in EPM1. 18 Moreover, seizures induce upregulation of CSTB mRNA and protein in rats.…”
Section: Introductionmentioning
confidence: 99%
“…16 The mice also show loss of cerebellar granule cells due to apoptotic cell death, 16 neuronal atrophy and apoptosis outside the cerebellum and gliosis. 17 In mice double-deficient for CSTB and cathepsin B, the amount of cerebellar apoptosis is significantly decreased, suggesting that cathepsin B contributes to the apoptotic phenotype in EPM1. 18 Moreover, seizures induce upregulation of CSTB mRNA and protein in rats.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that aldolase A and enolase 1 are transcribed in response to hypoxia (Semenza et al, 1996). Another protein up-regulated on treatment of NHA with Δ 9 -THC is cystatin B, important in maintaining normal neuronal architecture and size (Shannon et al, 2002). Brains of cystatin B deficient, adult mice are smaller than normal controls, and this size difference is paralleled by low body weight, a greater density of neurons in the cerebellar granular cell layer, as well as an increased susceptibility of granule cells to undergo apoptosis (Lieuallen et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Из-за своей важной функции они включаются в различные патофизиологические процессы, включая болезнь Альцгеймера [16], церебральную амилоидную ангиопатию [17] и другие нейродегенеративные заболевания [25].…”
Section: длина волны нмunclassified